Women Representatives in Britain, France, and the United States - Applewhite, Harriet Branson (Palgrave Macmillan, 2015)
"This book compares British, French, and American legislative debates on woman suffrage and women's rights. Beginning with an analysis of Tocqueville and J.S. Mill on the impact of suffrage, the book continues with analysis of floor debates, comparing gender style, the French on parity and the Americans on the ERA and concluding with modern debates"–
Keywords: France; Women; France; Women legislators; Great Britain; Women; Great Britain; Women legislators; History; Women; Suffrage; United States; United States; Women legislators; Women; dept.psc; faculty_collection

Professional Pathways to the Presidency - Marchant-Shapiro, Theresa (Palgrave Macmillan, 2015)
"During presidential elections a quadrennial debate emerges which, although it differs in the particulars, reflects the same structure in each reincarnation. Although the issue positions taken by the candidates vary over the years, their claim to qualification for the presidency follows a common pattern. Each candidate discusses his or her prior experience as preparation for one or more of the requirements of the office and then lays claim to the legacy of one of the great presidents who followed the same trajectory to the White House.Missing from this debate is a systematic analysis of how different job experiences prepared the population of all presidents for service. For each of the greats who followed a particular pathway to the presidents there is a failure who shared the pathway. In this book I combine the quantitative evaluation of presidential performance with mixture of qualitative and quantitative analyses of professional qualifications. The recent C-SPAN surveys provide us with a nuanced measure of presidential performance by asking historians to rate the Presidents on ten constituent attributes of: Public Persuasion, Moral Authority, Relations with Congress, Performance within Context of Times, Crisis Leadership, International Relations, Vision/Setting an Agenda, Economic Management, Administrative Skills, and Pursued Equal Justice for All. The sub-score for 'Relations with Congress' measures how well the president performs as 'legislator-in-chief' so that I can see whether former legislators work better with congress. Similarly the measure of 'Administrative Skills' indicates whether experience as a governor leads to better performance as the national chief executive. The evaluation of 'Economic Management' looks at whether those presidents with business experience do a better job in dealing with the economy. C-SPAN's nuanced measure of presidential performance allows a more careful evaluation of how prior experience affects particular aspects of presidential greatness than was previously possible"–, "Presidential hopefuls frequently claim they are qualified because their job experience is the same as a great president. However they ignore the failed presidents who shared the same pathway. This book evaluates all the presidents systematically to determine how prior professional experience influences presidential performance"–
Keywords: History; Vocational qualifications; Political aspects; Presidents; United States; dept.psc; faculty_collection

Presidential nominations in a Polarized Party System: The Republican primaries of 2012 - Paulson, A.C. (Winning the Presidency 2012, 2015)
Journal Abbreviation: Win. the Pres. 2012
Keywords: dept.psc